Analisis Manajemen Layanan E-learning Qualitiva SMK Negeri 1 Palembang Menggunakan Framework ITIL - sritari utami (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The world of education at this time has implemented information technology because of the demands of the globalization era in the implementation of the learning process. One of the applications of information technology in the world of education is a distance learning system or often referred to as E-learning where the teaching and learning process is carried out without having to meet face to face by utilizing the internet network and computer networks, the learning process is supported by communication facilities and technology through digital media. SMKN 1 Palembang is a vocational school that has implemented E-learning called Qualitiva. Since its implementation, an analysis has never been carried out to measure the maturity level of service management for the functions in Qualitiva, so it is not yet known how far E-learning has provided services that support the learning process. This study aims to measure the maturity level of service management in E-learning Qualitiva SMKN 1 Palembang using the ITIL Version 3 framework with the Service Operation domain. From the results of distributing questionnaires to 99 respondents consisting of students and teachers, it was found that the overall Qualitiva maturity level of SMKN 1 Palembang is 2.82 which means it is at level 3, namely defined. While the expected maturity level is level 4, namely managed, GAP analysis is worth 1.17. Several recommendations are given by the author to the school in the hope of achieving the desired level according to the ITIL framework. Keywords: Learning, Maturity Level, ITIL Version 3, Domain Service Operation